2007
DOI: 10.1002/mawe.200700194
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime‐determining spalling mechanisms of NiCoCrAlRE / EB‐PVD zirconia TBC systems

Abstract: The mechanisms that control the lifetime of thermal barrier coating (TBC) systems have been traced by two particular overlay bondcoats serving as model systems: superalloy pins (IN100, CMSX-4) with two alternative NiCoCrAlRE (RE: Hf, Y) bond coat compositions (i) NiCoCrAlY without and (ii) with co-dopants of silicon and hafnium. On top an electron-beam physical-vapor deposited (EB-PVD) yttria partially stabilized zirconia (YPSZ) TBC commonly mixed with 2 wt.% hafnia, or, rarely with 10 wt.%, was applied. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(35 reference statements)
0
2
0
2
Order By: Relevance
“…1 and 2 that only a handful of coating lives lie appreciably above the projected 7 μm boundary. It has been discussed that the activation energy surmised from TBC life correlated with that obtained by oxidation and diffusion in alumina [34]. In that regard, the 382 kJ/mol value obtained in Eq.…”
Section: Eb-pvd Tbc Fct Life On Nicocraly Bond Coatsmentioning
confidence: 68%
See 1 more Smart Citation
“…1 and 2 that only a handful of coating lives lie appreciably above the projected 7 μm boundary. It has been discussed that the activation energy surmised from TBC life correlated with that obtained by oxidation and diffusion in alumina [34]. In that regard, the 382 kJ/mol value obtained in Eq.…”
Section: Eb-pvd Tbc Fct Life On Nicocraly Bond Coatsmentioning
confidence: 68%
“…One of these studies systematically varied the Co content of a 3rd generation (high Re) composition and found that a low 2 wt.% Co alloy provided the maximum TBC life compared to 8 or 12 wt.% Co [30]. Other studies employed NiCoCrAlY bond coats [32][33][34][35] (Kim, Nijdam, Schulz, and coworkers) or a Pt coating over NiCoCrAlY(Ta) bond coat [36][37][38] (Yanar, Vande Put, and coworkers).…”
Section: Overview Of Fct Studies Citedmentioning
confidence: 99%
“…Гафний концентрируется преимущественно на поверхности покрытия в виде оксидов (светлых фаз), образующихся в процессе окисления. Структуры TGO на модифицированном покрытии подтверждают тот факт, что активные элементы (иттрий, гафний, цирконий) образуют сегрегации в виде соединений под пленкой TGO, а избирательное окисление их на внешней поверхности связующего слоя приводит к формированию локальных прикреплений, обеспечивающих механическое сцепление защитной пленки (и керамики) с подслоем, тем самым улучшая ее адгезионную прочность [11,14]. Формирование неравномерной границы раздела связующий слой/TGO может увеличивать сопротивление против распространения трещины при термоциклических испытаниях ТЗП.…”
unclassified
“…8, а, в, д). Эта особенность рассмотрена в работах [12,14,15,18,19]. В связующем слое с повышенным (за счет модифицирования активным элементом гафнием) пределом текучести могут уменьшаться или предотвращаться амплитудные изменения морщинистости поверхности в процессе термоциклирования [20].…”
unclassified